Rapid Rebound of a Preexisting CXCR4-tropic Human Immunodeficiency Virus Variant After Allogeneic Transplantation With CCR5 Δ32 Homozygous Stem Cells. (18th July 2018) - Verheyen, Jens; Thielen, Alexander; Lübke, Nadine; Dirks, Miriam; Widera, Marek; Dittmer, Ulf; Kordelas, Lambros; Däumer, Martin; de Jong, Dorien C M; Wensing, Annemarie M J; Kaiser, Rolf; Nijhuis, Monique; et al.
Abstract: Allogeneic stem cell transplantation (alloSCT) of homozygous CCR5 Δ32 stem cells once resulted in the cure of human immunodeficiency virus (HIV) infection. We have recently reported a viral breakthrough in a similar setting. Here, we demonstrate that the rapid rebound after alloSCT was related to a highly replicative CXCR4-tropic HIV variant, which could already be detected before alloSCT.